2016
DOI: 10.1007/s00280-016-3034-6
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone I induces apoptosis and pro-survival autophagy in gastric cancers

Abstract: Tanshinone I induced apoptosis and pro-survival autophagy via inhibiting Bcl-2 expression on gastric cancer, and the combination of chloroquine and Tanshinone I could inhibit tumor growth more efficiently than monotherapy, which might be considered as an effective strategy for the treatment for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…Despite multibiological activities of Tan I such as anti‐inflammatory (Park et al, ), antitumor (Jing et al, ; Lu, Wang, & Wang, ; Zhou, Zhang, Wang, & Sun, ), and antibacterial effect (Lee, Lee, Noh, & Hong, ), its antitumor mechanism is not fully understood compared with another component Tan IIA from Dansen. Thus, in the current study, the underlying mechanisms of Tan I from S .…”
Section: Discussionmentioning
confidence: 99%
“…Despite multibiological activities of Tan I such as anti‐inflammatory (Park et al, ), antitumor (Jing et al, ; Lu, Wang, & Wang, ; Zhou, Zhang, Wang, & Sun, ), and antibacterial effect (Lee, Lee, Noh, & Hong, ), its antitumor mechanism is not fully understood compared with another component Tan IIA from Dansen. Thus, in the current study, the underlying mechanisms of Tan I from S .…”
Section: Discussionmentioning
confidence: 99%
“…In GC, Jing et al first reported that TSN induced apoptosis and growth inhibition in vitro and in vivo . Subsequent research showed that TSN could reverse the malignant phenotype of GC cells and induce pro-survival autophagy in GC cells (22,23). In accordance with these studies, our research found that TSN inhibited the proliferation and migration ability of SGC-7901 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was detected using cell counting kit 8 (CCK) assay [15]. Cells exposed to media with different pH values (6.0 and 7.4) were inoculated in 96-well culture plates at a density of 4×10 3 per well.…”
Section: Cck8 Assay For Cell Viabilitymentioning
confidence: 99%